THE INFLUENCE OF HUMAN RESOURCE COMPETENCE, INFORMATION TECHNOLOGY USE AND DATA RECONCILIATION ON QUALITY OF FINANCIAL STATEMENTS OF WORK UNITS IN THE MINISTRY OF RELIOGIOUS AFFAIRS PARTNER OF STATE TREASURY SERVICE OFFICE IN TEBING TINGGI - rahmayani, siti (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research was to analyze simultaneously and partially the influence human resource competency, information technology use and data reconciliation on quality of the financial statementsof the work units in the Ministry of Religious Affairs, a partner of SKPPN (State Treasury Service Office) in Tebing Tinggi. The population was 74 administrators of the financial statements concisting of PPK and computer data recorder in the work units in the Ministry of Religious Affairs, a partner of KPPN in Tebing Tinggi. The samples were taken by employing census method. The research used primary data collected through questionnaires. It distributed 74 questionnaires and 72 questionnaires were returned. Multiple Regression analysis was applied as the data analysis method. The data were processed by using SPSS (Statistical Package For Social Science) version 23. The results of the research demonstrated that simultaneously, human resources competency, information tecnology use, and data reconciliation influenced significantly the quality of financial statements of the work units work units in the Ministry of Religious Affairs a partner of KPPN Tebing Tinggi. Partially, human resource competency, information technology use and data reconciliation had a positive and significant influence on quality of the financial statements of work units in the Ministry of Religious Affairs, partner of KPPN Tebing Tinggi